The life of politics: the compositional history of The Life of Poetry and Muriel Rukeyser's changing appraisal of emotion and belief. Issue 7 (9th August 2018) - Keenaghan, Eric
ABSTRACT: Between 1940 and 1949, the period when Muriel Rukeyser composed The Life of Poetry, the United States moved from pre-war into wartime and then post-war periods. Rukeyser's politicised poetics shifted in response to these changing conditions. A bibliographic approach that reads the book through Rukeyser's original lectures' extant unpublished scripts, drafts and reading notes, and other archival sources illuminates how her increasing emphasis on emotion and psychology, coupled with her de-emphasis of belief, inflected her leftist poetics.